Peran Regulasi Emosi Dalam Profesionalisme Guru - Mochammad Ramdan Samadi; Laesti Nurishlah; Ani Sri Mulyani (TA'DIB: Jurnal Pendidikan Agama Islam, 2023)
This research investigates the role of emotion regulation skills on teacher professionalism. This study highlights the importance of emotion regulation skills for teachers in creating a positive learning environment, building strong relationships with students, and increasing teaching effectiveness. A lack of emotional regulation can undermine teachers' professionalism and the quality of their teaching. This research uses a qualitative literature study method on data relating to emotional regulation and teacher professionalism. Literature study is used as a research method in an effort to collect, analyze and synthesize findings and understanding that have been developed in scientific literature regarding the role of emotional regulation and teacher professionalism. The practical implications of these findings emphasize the need to support teachers in developing their emotion regulation skills to create a conducive learning environment and improve the overall quality of education.